Are Program Participants Good Evaluators? - Jeffrey A. Smith; Alexander Whalley; Nathaniel T. Wilcox (Institute of Labor Economics (IZA), 2020)
How well do program participants assess program performance ex-post? In this paper we compare participant evaluations based on survey responses to econometric impact estimates obtained using data from the experimental evaluation of the U.S. Job Training Partnership Act. We have two main findings: First, the participant evaluations are unrelated to the econometric impact estimates. Second, the participant evaluations do covary with impact proxies such as service intensity, outcome levels, and before-after outcome differences. Our results suggest that program participants behave as 'lay scientists' who seek to estimate the impact of the program but face cognitive challenges in doing so.
Keywords: I28; J24; C83; 330; program evaluation; participant evaluation; surveys